Digital Echoes Spaces for Intangible and Performance-based Cultural Heritage (Springer International Publishing, 2018)
This book explores the interplay between performing arts, intangible cultural heritage and digital environments through a compendium of essays on emerging practices and case studies, as well as critical, historical and theoretical perspectives. It features essays that engage with varied forms of intangible cultural heritage, from music and storytelling to dance, theatre and martial arts. Cases of digital technology interventions are provided from different geographical and cultural settings, from Europe to Asia and the Americas. Together, the collection reflects on the implications that digital interventions have on intangible cultural heritage engagements, its curation and transmission in diverse localities. The volume is a valuable resource for discovering the multiple ways in which cultural heritage is mediated through digital technologies, and engages with audiences, artists, users and researchers.